ADVJRNL 2018
DOI: 10.5399/osu/advjrnl.1.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing and Intervening in Bias Incidents in the Academic Workplace: A Self-Categorization Theory Perspective

Abstract: In higher education, the problem of bias is under increasing scrutiny. Observers have noted the potential for bias incidents to corrode workplace climate, particularly in fields where women and faculty of color are underrepresented (Carnes, Devine, Isaac, Manwell, Ford, Byars-Winston, Fine, & Sheridan, 2012). Extant research has examined workplace bias incidents and their effect on perceptions of department climate, as well as how implicit biases influence candidate evaluation in recruitment and promotion proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Furthermore, data suggest that when bystander training is designed to be interactive and engaging, participants’ reactions to such programming are positive (Shea et al, 2019). Such programming can increase the likelihood that bystanders will recognize a bias incident when it occurs (Shea et al, 2018), a critical first step in a faculty member’s decision to intervene. For example, in a study of the use of interactive theater to train faculty on bias in faculty searches, Shea et al (2019) found that the representation of women faculty increased significantly following the program’s implementation, and a significant portion of this increase was directly attributable to the workshop training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, data suggest that when bystander training is designed to be interactive and engaging, participants’ reactions to such programming are positive (Shea et al, 2019). Such programming can increase the likelihood that bystanders will recognize a bias incident when it occurs (Shea et al, 2018), a critical first step in a faculty member’s decision to intervene. For example, in a study of the use of interactive theater to train faculty on bias in faculty searches, Shea et al (2019) found that the representation of women faculty increased significantly following the program’s implementation, and a significant portion of this increase was directly attributable to the workshop training.…”
Section: Discussionmentioning
confidence: 99%
“…Acts of incivility are most often committed by people who feel a sense of power over targets, who tend to be minoritized based on their gender, race, or ethnicity (Cortina et al, 2013). In studies of campus climate, faculty who identified as women, people of color, and lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) were significantly more likely to report witnessing a bias incident at their university (Shea et al, 2018). This article focuses on one particular type of workplace incivility perpetrated against individuals because of their social group membership status, which we label bias incidents .…”
Section: Bias Incidents As Threat Appraisalsmentioning
confidence: 99%
“…Given universities' growing commitments to diversity, it is imperative that they invest in initiatives that encourage intervention in bias incidents. Faculties from historically and commonly excluded groups are more likely to report negative experiences, less influence and unfair treatment (Shea et al , 2018). If universities aim to retain faculty from commonly excluded groups, particularly in the STEM disciplines where such underrepresentation is most acute, it is vital to train faculty to intervene in appropriate ways to stop bias incidents from creating a chilly climate.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we believe their typology is a logical theoretical framework on which to ground this effort, which centers on reacting to bias incidents more broadly. Bias incidents refer to acts of incivility, perpetrated by people who feel a sense of power over targets that tend to be minoritized based on their gender, race, ethnicity or sexual orientation (Shea et al , 2018). Bias incidents are often prompted by an unconscious, stereotypical, prejudicial belief or oversimplified generalization about a person or group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation